2017
DOI: 10.1007/s13224-017-1024-1
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Multifetal Reduction: A Hospital-Based Study

Abstract: Favorable pregnancy outcomes can be achieved after multifetal reductions during first trimester in higher-order multiples, but the procedure is not totally safe.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…11 High order pregnancies sometimes carries a higher risk of prenatal outcomes, significant complications of prematurity and most common is preterm labour. 12 The data of this study showed that the outcome of triplet pregnancies reduced to twins differ substantially from the non-reduced group. The information regarding the outcome of twin pregnancies after reduction is based on limited subjects.…”
Section: Discussionmentioning
confidence: 64%
“…11 High order pregnancies sometimes carries a higher risk of prenatal outcomes, significant complications of prematurity and most common is preterm labour. 12 The data of this study showed that the outcome of triplet pregnancies reduced to twins differ substantially from the non-reduced group. The information regarding the outcome of twin pregnancies after reduction is based on limited subjects.…”
Section: Discussionmentioning
confidence: 64%
“…8 In our case, patient was counselled about the risk of higher spontaneous abortions and preterm labour rates in multiple pregnancies and was offered the option of fetal reduction. 9 The risks of procedure was explained to the patient and informed consent was obtained. 10 Haiyan et al, reported a case of triplet pregnancy, during first trimester management options included fetal reduction of two twins by fetal intracardiac injection of KCl by ultrasound guided trans abdominal procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, using KCl becomes more imperative with advancing gestational age, mainly when the goal is to terminate larger fetuses. Significantly, this method is associated with favorable pregnancy outcomes when applied for fetal reduction in multifetal pregnancies [ 41 ]. Moreover, a compelling case report contributes to the growing body of evidence by detailing the successful non-surgical management of a heterotopic abdominal pregnancy.…”
Section: Reviewmentioning
confidence: 99%
“…A range of methods exists for fetal reduction, encompassing transabdominal, transcervical, or transvaginal approaches, along with chemical, thermal, radiofrequency, or laser techniques, contingent upon factors such as chorionicity [ 39 ]. MFPR is designed to decrease higher-order pregnancies, enhancing perinatal outcomes [ 41 ]. In the context of unruptured HP, the suggestion to use KCl infusion for fetal reduction has been made.…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation